The Relationship Between Age And Parity With The Incidence Of Prolonged Labor at Jemursari Islamic Hospital Surabaya in September-November 2021 - Aulia Savitri; Queen Khoirun Nisa' Mairo; Mamik; Astuti Setiyani (Jurusan Kebidanan Politeknik Kesehatan Kemenkes Surabaya, 2022)
Prolonged labor is one of the complications in labor that can harm the moter and also the fetus, according to the data obtained, the number of deliveries at the Jemursari Islamic Hospital in Surabaya is 188 out of 1000 deliveries.The purpose of this study want to know the relationship between age and parity with the incidence of prolonged labor at Jemursari Islamic Hospital Surabaya in September-November 2021. This type of this research is analitic survey with used quantitative data or secondary data with a Cross Sectional approach tested with Chi Square analysis test and techniques sampling using simple random sampling technique with a population of 277 and then obtained a sample of 72 respondents data. The results showed there is no significant relationship between age and the incidence of prolonged labor at Jemursari Islamic Hospital Surabaya and there is a significant relationship between parity and the incidence of prolonged labor at Jemursari Islamic Hospital Surabaya. So that the suggestions that can be given are that it is hoped then can be used as a reference as a factor related to old parturition and the scope of the research is expanded.